2022
DOI: 10.3389/fphar.2022.828161
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Relieves Atherosclerosis and Hepatic Steatosis via MAPK/NF-κB Signaling Pathway in LDLR−/− Mice

Abstract: Astragaloside IV (AS-IV) is the main active compound of Astragalus membranaceus. In this study, we investigated whether AS-IV could attenuate atherosclerosis and hepatic steatosis in LDLR−/−mice and its potential mechanisms. After 12 weeks of high fat diet, the LDLR−/−mice were randomly divided into four groups. Then, the mice were administrated with 0.9% saline or AS-IV (10 mg/kg) or atorvastatin (1.3 mg/kg) for 12 weeks. Serum lipid profiles and inflammatory cytokines were detected by ELISA, hepatic TC and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Geniposide combined with Panax notoginsenoside R1 inhibits the secretion of serum inflammatory and oxidative stress factors by inducing activation of the Nrf2 signaling pathway and synergistically reduces blood lipid levels and inhibits plaque formation (Liu et al, 2021). Other natural saponins, such as amygdalin (Wang et al, 2020), astragaloside IV (Zhang et al, 2022a), and saikosaponin (Yang et al, 2017) can also protect against AS plaques by modulating the MAPK/NF-κB signaling pathway and reducing inflammatory factors and oxidative stress responses.…”
Section: Saponinsmentioning
confidence: 99%
“…Geniposide combined with Panax notoginsenoside R1 inhibits the secretion of serum inflammatory and oxidative stress factors by inducing activation of the Nrf2 signaling pathway and synergistically reduces blood lipid levels and inhibits plaque formation (Liu et al, 2021). Other natural saponins, such as amygdalin (Wang et al, 2020), astragaloside IV (Zhang et al, 2022a), and saikosaponin (Yang et al, 2017) can also protect against AS plaques by modulating the MAPK/NF-κB signaling pathway and reducing inflammatory factors and oxidative stress responses.…”
Section: Saponinsmentioning
confidence: 99%
“…The characteristics of a vulnerable plaque include a low fibrous cap area ( 28 , 29 ). Then the collagen content was detected by Masson staining to explore the effect of THD on the stability of atherosclerotic plaques.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that astragaloside IV is able to inhibit liver inflammation via mitogen-activated protein kinase (MAPK)/nuclear factor kappa-B (NF-κB) signaling pathway, which in turn reduce lipid levels, hepatic steatosis in hyperlipidemic mice ( Zhang Y. et al, 2022 ). Astragaloside IV significantly reduces body weight, white fat and liver/body weight ratio in senescent mice by targeting mitochondrial activity, and promotes fatty acid in white adipose tissue mobilization in aging mice ( Luo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%